Food Behavior, Oral Hygiene and Dental Problems am ong the Children (6-11 Years) at Dhaka City in Bangladesh - Islam, Md Tazul; Hoque, SM Rezaul; Gulshan Ara, Jubaida; Bhuyan, M A H (Bangladesh Journal of Nutrition, 2014)
A descriptive type of cross sectional study was carried out to assess the prevalence of dental diseases and to find out the relationship between dental diseases and the regular food intake pattern of children aged 6-11 years in Dhaka city. Oral examination was done to identify dental diseases for a sample of 123 children. A structured questionnaire was used for collecting relevant information. Result shows that the most prevalent dental disease among this age group was dental caries (52.8%) which was found to be decreased with the increase of age (P value= 0.005). Any type of dental disease was significantly related to consumption of excessive carbohydrate intake in daily meal (P value= 0.03). Those, who consume more than 300g of carbohydrate and sticky food, became more susceptible to dental disease and it was found to be 78.9%. The prevalence rate of dental disease was found to be high (95.1%) in higher economic group whose family income (monthly) is more than 18000tk. Bottle feeding, the major cause of teeth decay among children, were found to be significantly related with dental diseases (P value= 0.01). Only 13.8% used paste or powder containing Ca and/or F had less diseases percentage (P value= 0.002). Following the correct manner of tooth brushing (right way), brushing frequency (two or more) and gargling (regularly) reduced the probability of dental problems. The study also revealed that children had less dental problems (33.3%) whose parents had little preventive knowledge of dental diseases. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 25-34